Sensory profiles and skin innervation of patients with painful and painless neuropathies - Üçeyler, Nurcan; Vollert, Jan; Broll, Barbara; Riediger, Nadja; Held, Melissa; Saffer, Nadine; Schubert, Anna-Lena; Siedler, Gabriela Anja; Sommer, Claudia (Pain, 2018)
AbstractWe assessed pain characteristics and sensory profiles of a large and extensively phenotyped cohort of patients with polyneuropathies (PNPs) and small fiber neuropathy (SFN) using quantitative sensory testing (QST). Our aim was to detect potentially discriminative QST profiles of patient subg
Gesehen am 19.06.2019